MANAGEMENT OF RECEIVABLES OF THE ENTERPRISE AS A TOOL OF ANTI-CRISIS FINANCIAL MANAGEMENT - Герасименко, Ирина; Синица, Руслан (SWorldJournal, 2021)
The main cause of the crisis is the low level of management and the inability of enterprises to effectively and timely manage current assets. The receivables management system can rightly be defined as an integral part of the general anti-crisis managemen